Depressive Symptoms, Gender, and Ethnicity: An Exploratory Study among Cross Ethnic Adolescents in Sarawak, Malaysia - Siti Raudzah, Ghazali; Azizah, Azhar (Malaysian Institute for Research in Youth Development, Ministry of Youth and Sports Malaysia, 2015)
Depression and suicide among teenagers in Malaysia is a growing concern (Kok & Goh, 2011). The objectives of this study were to determine the prevalence of depressive symptoms and its association with demographic characteristics among secondary school students. A cross sectional survey was employed; 386 students were recruited, aged 13 to 16-years-old. Stratified random sampling was performed to choose several secondary schools from rural and urban areas of Sarawak, East Malaysia. The rate of depressive symptoms among secondary school students in this area was 7.8% (30). Among those who reported having depressive symptoms, 43.3% (13) had thoughts of commiting suicide, 40% (12) had suicidal ideation, and 16.7% (5) never had any suicidal thought or ideation. Students of Chinese ethnicity were significantly more depressed than other ethnicities. Students who had only one sibling were more depressed than those who had more than one sibling. Students who were staying in urban areas were more depressed compared to students staying in rural areas. While previous studies have reported that girls are more depressed than boys, no significant difference in depressive symptoms was found between genders. Type of schooling, living arrangement, family history of depression, and staying with extended family members had no significant association with depressive symptoms.